Survival of patients with stage I epithelial ovarian carcinoma, 1981-1985 at Ramathibodi Hospital. - V. Linasmita (2018)
Thirty-one patients with stage I epithelial ovarian carcinoma were treated during 1981 and 1985. Fourteen cases were stage Ia, two stage Ib and fifteen stage Ic. Twenty-eight cases had at least a TAH with BSO. Postoperatively, twenty-one patients received melphalan as adjuvant chemotherapy (mean of 11 courses). There were 8 patients who received no adjunctive therapy. One patient had radiation treatment and the remaining one received hormonal treatment. Eighty-seven per cent (27 out of 31) of tumors were of borderline type or well differentiated, four were moderately well differentiated. Poorly differentiated tumor was not observed in our series. The follow-up (31 patients) ranged from 0-82 months with a median of 52 months. The overall 5-year survival was 95.4 per cent. There was one reported death whose tumor was stage Ic grade 1 and who had received melphalan postoperatively. No serious adverse effects were noted among patients who received melphalan.